Để A nhận gái trị nguyên thì
\(\Leftrightarrow x-5⋮x-3\)
\(\Leftrightarrow\left(x-3\right)-2⋮x-3\)
\(\Leftrightarrow2⋮x-3\)
Vì \(x\inℤ\Leftrightarrow x-3\inℤ\)'
\(\Leftrightarrow x-3\in\)Ước nguyên của 2
\(\Leftrightarrow x-3\inƯ\left(2\right)=\left\{\pm1;\pm2\right\}\)
Ta có bảng giá trị
x-3 | -1 | -2 | 1 | 2 |
x | 2 | 1 | 4 | 5 |
Vậy \(x\in\left\{2;1;4;5\right\}\)Thì A nhận giá trị nguyên
ta có: \(A=\frac{x-5}{x-3}=\frac{x-3-2}{x-3}=\frac{x-3}{x-3}-\frac{2}{x-3}=1-\frac{2}{x-3}\)
Để A nhận giá trị nguyên
\(\Rightarrow\frac{2}{x-3}\inℤ\)
\(\Rightarrow2⋮x-3\Rightarrow x-3\inƯ_{\left(2\right)}=\left(2;-2;1;-1\right)\)
nếu x -3 = 2 => x = 5 (TM)
x -3 = -2 => x = 1 (TM)
x -3 = 1 => x = 4 (TM)
x -3 = -1 => x = 2
KL: \(x\in\left(5;1;4;2\right)\)
Để \(\frac{x-5}{x-3}\in Z\)thì \(x-5⋮x-3\)
Ta có : \(x-5=x-3-2\)
Ta thấy \(x-3⋮x-3\)=> \(-2⋮x-3\)
=> \(x-3\inƯ\left(-2\right)=\left\{1;-1;2;-2\right\}\)
+) \(x-3=1\) +) \(x-3=-1\)
x = 1 + 3 x = -1 + 3
x = 4 x = 2
+) \(x-3=2\) +)\(x-3=-2\)
x = 2 + 3 x = -2 + 3
x = 5 x = 1
Vậy \(x\in\left\{4;2;5;1\right\}\)